PERLINDUNGAN HUKUM PEMEGANG HAK ATAS TANAH BERDASARKAN JUAL BELI DI BAWAH TANGAN (Studi Kasus di Desa Boncah Mahang, Kecamatan Bathin Solapan, Kabupaten Bengkalis) - M. Shihab Rozi; Hayatul Ismi; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This study aims to find out why the practice of buying and selling land infront of the village head is often carried out by the community in Boncah MahangVillage, Bathin Solapan District, Bengkalis Regency and what efforts must bemade so that the community buys and sells land rights in accordance withGovernment Regulation number 24 of 1997 so that obtain permanent legal forceas well as protection for the sale and purchase of land rights which have onlybeen carried out privately.The type of research used is sociological or empirical legal research.Sociological research is research on law observing the characteristics of acommunity's behavior in an area in an aspect of social life if we look at the factson the ground. The results of this study are first to find out legal protection bysomeone who buys and sells land privately in order to get his rights back over thedispute, the second research results find that the things that result in buying andselling under the hands in Boncah Mahang Village are: habit factor, expensivecost factor, factor of the distance of the national land agency agency.Keywords: Protection-Purchasing of Land-Underhand